The American flag - Quiri, Patricia Ryon (New York Children's Press, 1998)
Describes the history and symbolism of the American flag
American Corner
Includes bibliographical references (p. 44) and index
11
Keywords: Flags -- United States -- Juvenile literature; Flags -- United States